Official Supported Export Credits Developments and Prospects. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1990)
This paper presents report on a number of countries in Asia that have made substantial use of agency credits, including the quasi-concessional financing available through mixed credit s. Through their willingness to grant comprehensive relief on a case-by-case basis, official creditors have responded flexibly to the needs of individual countries. The ability of export credit agencies to also provide substantial new financing to rescheduling countries has depended on the strategy of debt subordination achieved through fixing cutoff dates. As to the role of export credits at present, when the debt strategy's continuing emphasis on new money flows is being supplemented by debt reduction, the debt subordination strategy followed by export credit agencies has left them well positioned to provide necessary new financing for middle-income countries pursuing strong adjustment. In heavily indebted low income countries, whose needs for project finance should most appropriately be met by concessional finance, export credit agencies continue to play an important role in supporting essential short-term credits.